MENINGKATKAN MOTIVASI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN COURSE REVIEW HORAY (CRH) KOMPETENSI DASAR SISTEM POLITIK INDONESIA KELAS X-RPL2 SMK NEGERI 4 BANJARMASIN - Hilal, Nurul (Pendidikan Kewarganegaraan, 2014)
Nurul Hilal, 2013. ImproveStudentMotivation through ModelImplementationCourse Review horay(CRH) Basis competence IndonesianPoliticalSystemClassX-RPL2 SMKNegeri 4Banjarmasin. Thesis, Program Study of Citizenship and Pancasila Education, Department of Social Sciences Education, Faculty of Teacher and Education Science, University of Lambung Mangkurat. Conselor (1)Acep Supriadi, (II) Dian Agus Ruchliyadi.Process in teaching and learning civics education at X-RPL2 class of SMK Negeri 4 Banjarmasin does not achieve the expected results. This condition cause by the students have low motivation that can be influence in quality of learning. It seem when process teaching and learning occurÂ  in the class the clever students more active than passive students. Therefore, the passive students who unable to understanding the material feel ashamed to ask and expressing their opinions because they feel not appreciated. Lack of democratic attitudes of students can be seen from the low student motivation democracy in discussion activities. Students pay less attention when teacher explained the material, just only some of them. Thus, its can be influence at learning outcomes.The objectives of this research are: (1) To determine the activity of teachers in implementation the learning material by course review horay (CRH) at X- RPL2 class of SMKN 4 Banjarmasin (2) To increase students motivation in learning civics democracy in the applying CHR at X-RPL2 class of SMKN 4 Banjarmasin (3) To improve student learning outcomes in applying CHR at X-RPL2 class of SMKN 4 Banjarmasin.Techniques data collection used in this class action research (PTK) is the observation, documentation and test results of study was conducted through several cycles, there are cycle I dan cycle II.The results of this research (1) Process teacher in teaching and learning by using CRH. In the first cycle of learning, teacher has enough qualified, and the second cycle the teacher has increased good qualifications (motivation democracy). (2) Increased studentsâ motivation democracy is very good with good qualifications. (3) Applying CRH in process teaching and learning can enhance democracy student motivation and student learning outcomes.Keyword :Â  Motivation, learning outcomes, CourseReviewhoray (CRH)